Contribution to the knowledge of the genus Iphiothe Pascoe, 1866 (Coleoptera: Cerambycidae: Lamiinae). 2. A new species from Borneo, with notes on the other members of the genus - A.I. Miroshnikov; D.J. Heffern (Кавказский энтомологический бюллетень, 2020)
Iphiothe pascoei Miroshnikov et Heffern, sp. n. is described from Borneo. It differs clearly from all members of the genus by the sharply dichromatic coloration of the legs and antennomere 3, the immaculate femora and tibiae, the very motley, spotted, light setation of the elytra, the shorter antennae of the male. The stability and reliability of the features previously indicated to distinguish I. criopsioides Pascoe, 1866 and I. malaccensis Miroshnikov, 2019, including in the habitus, the shape of the pronotum and elytra, the structure of antennomere 3 are shown. Iphiothe borneana (Breuning, 1976) is being recorded from East Malaysia for the first time.